The Geostrategic Importance of the Western Border Cities in Iraq: Safwan as a Model - Aswad AL.Ahbabi, Naseef Jasim; Hadi AL. Samarraie, Hind Ali (Journal of Tikrit University for Humanities, 2023)
The city of Safwan is one of the border cities with the State of Kuwait, where it constitutes a geostrategic importance in the strength of the Iraqi state, as the movement of nomads and commercial operations constitute the first nucleus for the emergence of the study area, and it became one of the important transportation stations in the region. This in turn gave it importance for being the cornerstone of the Iraqi-Kuwaiti relations politically and economically. In addition, it is the land bridge linking Iraq to the Arabian Gulf region, which gave it exceptional importance as it is Iraq's economic gateway and a theater for political events. It is the first to be affected by conflicts and political disputes to the period of economic openness towards the Arab Gulf after 2003 .